A cooperação como um elemento de construção do bem viver: uma análise sobre a iniciativa solidária Nossa Polpa na Comunidade de Barra - Ichu - BA - Carneiro, Osvaldo Júnior de Oliveira (2019)
Sharing with a proposal of competition centered on principles of solidarity in opposition to the title of competitiveness for all purposes, all present are verified, under the assumptions of the analytical key of Good Living, to what extent a solidarity initiative. quality of life of the cooperative women of NossaPolpa Group - Fruit Pulp Production Center, based in the community of Barra, belonging to the municipality of Ichu-Ba, was not integrated into the alternative economic system of solidarity economy. This research follows a descriptive approach, substantiated by a case study. Methodologically, for data collection the first data used a literature review, a document analysis, a little more than once, having as an analysis tool a matrix. SWOT FOFA, aiming at an understanding and description of the group. The research showed that there are some points that were compromised - but not impossible - the solidarity initiative. In addition, the space for growth and expansion of the possibilities of action of cooperatives, with consequent improvement of living standards. These vowels are very important for the development of other possibilities of existence.